Morphometric studies in rectal biopsy specimens from patients with ulcerative colitis: effect of oral 5 amino salicylic acid and rectal prednisolone treatment - Zaitoun, A M; Cobden, I; al Mardini, H; Record, C O (Gut, 1991)
Morphometric measurements were performed on rectal biopsy specimens from 10 normal control subjects and 33 patients with a relapse of distal ulcerative colitis before and after treatment for four weeks in a double blind controlled trial with oral eudragit S coated 5 amino salicylic acid (n = 12) or rectal prednisolone enemas (n = 15). Measurements were assessed using a computer aided measuring system and a counting technique. When untreated patients were compared with the control group there were significant decreases in the area and height of the surface epithelium, in the area of crypt epithelium, and in the ratios of goblet cells to epithelial cells and of surface epithelium to lamina propria. The vascular and lamina propria areas and the number of intraepithelial polymorphs were increased. Treatment with 5 amino salicylic acid and corticosteroids resulted in similar morphological improvements: there was an increase in the area and height of the surface epithelium and the ratios of surface epithelium to lamina propria and of surface to crypt cell height. The ratio of goblet cells to epithelial cells also increased after treatment, while the numbers of polymorphs in the surface and crypt epithelium and lumen decreased. In conclusion, computerised morphometry is valuable for the assessment of the treatment of patients with ulcerative colitis and that in the doses used both treatments were of similar efficacy.